PENGARUH PENGGUNAAN BAHAN BAKU TERHADAP KARAKTERISTIK VEGETABLE ABON - Mirratunnisya Mirratunnisya; Putri Fara Dilla; Repka Natalia; Iffah Muflihati (Universitas Darussalam Gontor, 2021)
Floss is a food that is generally made from meat, but floss can also be developed from local food ingredients that have fiber-like meat such as kluwih, breadfruit, and jackfruit. Making floss from local food can increase food diversification and its economic value. The purpose of this study was to determine the sensory and chemical characteristics of artificial flosses from kluwih, breadfruit, and jackfruit. This research used a completely randomized design with 3 types of the raw materials: kluwih, breadfruit, and jackfruit. The result of the water content test showed an average value of 3.47-3.65%. The results should that the floss from kluwih tended to be preferred by the panelists. The treatment of the use of different types of materials showed significantly different effects on moisture content, hedonic value and color of the vegetable floss.